The Irish in Manchester c.1750-1921 : Resistance, adaptation and identity - Busteed, M. A. (Mervyn Austen), 1944- (Book collections on Project MUSE., 2016)
The book examines the development of the Irish community in Manchester, one of the most dynamic cities of nineteenth-century Britain. Based on research into a wide variety of local sources, it examines the process by which the Irish came to be blamed for all the ills of the industrial revolution and the ways in which they attempted to cope with a sometimes actively hostile environment. It discusses the nature and degree of residential segregation in one notable Irish district and the role of the Catholic Church as a source of spiritual comfort and the base for a dense network of mutual aid and.